(untitled) (Experimental biology, 2021)
The article presents a faunistic and ecological review of useful hemipteran insects on the territory of the State National Natural Park "Altyn-Emel" in 2020-2021. The fauna of zoophages and zoophytophages, which is important in the natural regulation of the number of harmful insects and ticks, is presented. As a result of the study, 67 species from 4 families of terrestrial hemipteran insects were identified. According to the results of research, species from the family Nabidae are known: 3 genera - Prostemma (1 species), Nabis (12 species), Himacerus (1 species) and the family Anthocoridae: 3 genera - Anthocoris (6 species), Temnostethus (1 species), Orius (7 species) – 14 species each, from the family Reduviidae: 7 genera - Empicoris (1 species), Holotricius (1 species), Reduvius (1 species), Oncocephalus (1 species), Coranus (3 species), Rhynocoris (2 species), Vachiria (1 species) – 10 species, from the family Miridae: 11 genera - Deraeocoris (5 species), Malacocoris (1 species), Pilophorus (2 species), Atractotomus (1 species), Campylomma (2 species), Myrmecoris (1 species), Phytocoris (5 species), Globiceps (2 species), Psallus (7 species), Cyllecoridea (1 species), Blepharidopterus (2 species) – 29 species. Of these, 38 species are zoophages (species of the family Nabidae, Anthocoridae, Reduviidae), and 29 species are zoophytophages (species of the family Miridae). Predatory bedbugs are found everywhere throughout the summer, they feed on eggs, larvae and adults of various arthropods in nature. Therefore, feeding on harmful insects and ticks, they regulate their number biologically, thereby bringing great benefits to nature.